2001
DOI: 10.1097/00007691-200106000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as an Alternative Body Fluid for Therapeutic Drug Monitoring of the Nonnucleoside Reverse Transcription Inhibitor Nevirapine

Abstract: The objective of this study was to evaluate the applicability of saliva as an alternative body fluid for therapeutic drug monitoring of nevirapine. The pharmacokinetics of nevirapine in plasma and saliva during a dosing interval was assessed in HIV-1-infected patients taking nevirapine (200 mg twice daily) to explore the relation between the concentration of nevirapine in plasma and saliva. To validate the anticipated relationship prospectively, single, paired plasma and saliva samples were obtained from nevir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 7 publications
3
29
0
Order By: Relevance
“…Determination of EFV levels in human hair [7] and reports of determining nevirapine [8,10] and indinavir [24] from saliva have been published, but this study is the first validated LC-MS/MS method for the assay of EFV in saliva to be reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Determination of EFV levels in human hair [7] and reports of determining nevirapine [8,10] and indinavir [24] from saliva have been published, but this study is the first validated LC-MS/MS method for the assay of EFV in saliva to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) of antiretroviral (ARV) plasma concentrations can be useful in the optimization of HIV treatment [6,7], however, the collection of plasma is invasive, causes discomfort and is painful [8] especially in young children, opposed to the collection of saliva which can be done by noninvasive, painless methods and has a diminished risk of HIV transfer to the health care worker [8]. However, for the use of saliva for TDM, a confirmed relationship should exist between the concentrations of the drug in the different body fluid matrixes [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies investigated the use of saliva for therapeutic drug monitoring (TDM) and/or compliance control studies in HIV infected patients undergoing antiretroviral therapy (HAART) [3][4][5][6]. Rolinski and collaborators have shown a good correlation between plasma and salivary concentrations of zidovudine (ZDV) in ten HIV-infected patients suggesting that stimulated saliva might be an appropriate specimen for ZDV-TDM [3].…”
Section: Introductionmentioning
confidence: 99%